Improving Students' Mathematical Spatial Ability in the Spatial Geometry Course Using GeoGebra - Izzati, Nurma; Widyastuti, Widyastuti; Nurhadiansyah, Nurhadiansyah (MASI Mandiri Edukasi, 2024)
This study aims to determine students' responses to the use of GeoGebra in spatial geometry courses and to determine the difference in significant improvement between the spatial mathematical ability of students taught using GeoGebra and those of students taught conventionally. The design of this study is counterbalanced. The research population is all Mathematics Tadris UIN Siber Syekh Nurjati Cirebon students who take the spatial geometry course in the odd semester of the 2024/2025 Academic Year, which consists of 3 classes: A, B, and C. For the research sample, two classes were selected from the research population, class A was selected as experimental class 1, consisting of 25 students, and class B as experimental class 2, consisting of 28 students. The sample was selected using a cluster random sampling technique. The research instruments are questionnaires and tests. Data analysis was carried out on the average results of students' spatial mathematical ability tests in the spatial geometry course. The results of the study showed that most students gave a positive response to the use of GeoGebra in spatial geometry courses, with an average percentage of 93.51%, including the strong category and the increase in the spatial mathematical ability of students who used GeoGebra in the spatial geometry course was significantly higher than the improvement of the spatial ability of students who were taught conventionally.